Idiopathic Pulmonary Fibrosis in the Era of Antifibrotic Therapy: Searching for New Opportunities Grounded in Evidence - Robalo-Cordeiro, C (2017)
Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal lung disease that up to now has been associated with a poor prognosis. However, the results of the INPULSIS and ASCEND trials and the approval of nintedanib and pirfenidone have marked the beginning of a new era for IPF patients. Questions remain, however. Should these drugs be used earlier? What effect will they have on more severe disease? Will their effects last beyond the trial period? This manuscript is the outcome of a multidisciplinary meeting between pulmonology, radiology, and pathology clinicians on the use of antifibrotic agents in IPF. In our opinion, the existing data show that pirfenidone and nintedanib slow functional decline in early stages of disease. These drugs also appear to result in therapeutic benefits when administered to patients with advanced disease at diagnosis and maintain effective over time. The data also suggest that continuing antifibrotic therapy after disease progression may confer benefits, but more evidence is needed. Early diagnosis and treatment are crucial for reducing functional decline, slowing disease progression, and improving quality of life.